2014
DOI: 10.3109/13880209.2014.913297
|View full text |Cite
|
Sign up to set email alerts
|

Schizandra chinensisextracts induce apoptosis in human gastric cancer cells via JNK/p38 MAPK activation and the ROS-mediated/mitochondria-dependent pathway

Abstract: Objectives: This study investigates the mechanism of SCE-induced apoptosis in AGS human gastric cancer cells. Materials and methods: SCE concentrations from 100 to 400 mg/ml were used. Cell viabilities were determined using MTT assay. Members of the Bcl-2 family and Bax were detected by Western blotting. RT-PCR was performed to measure the expression level of the Fas/FasL pro-apoptotic genes.Results: SCE inhibited the proliferation AGS cells for 24 or 72 h (inhibition by 3.1% ± 5.2% at 100 mg/ml and 87.3% ± 7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…There are accumulating evidences that MAPK pathways including JNK, p38, and ERK are involved in cell survival and apoptosis in several cancer cells following exposure to various stimuli (Milone et al, ). Additionally, it was reported that ROS affects MAPK signaling (Kim et al, ; Weh, Aiyer, Howell, & Kresty, ), and also, intercellular ROS production induces MAPK activation during apoptosis (Hua et al, ; Y. Zhu et al, ). In this study, Tan I increased phosphorylation of p38 and JNK but not ERK in HCT116 and HT29 cells.…”
Section: Discussionmentioning
confidence: 99%
“…There are accumulating evidences that MAPK pathways including JNK, p38, and ERK are involved in cell survival and apoptosis in several cancer cells following exposure to various stimuli (Milone et al, ). Additionally, it was reported that ROS affects MAPK signaling (Kim et al, ; Weh, Aiyer, Howell, & Kresty, ), and also, intercellular ROS production induces MAPK activation during apoptosis (Hua et al, ; Y. Zhu et al, ). In this study, Tan I increased phosphorylation of p38 and JNK but not ERK in HCT116 and HT29 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that activation of MAPK, especially the JNK/p38-MAPK is associated with gastric cell apoptosis induction and considered as a promising therapeutic target (Chun et al 2013;Kim et al 2015). The JNK/p38-MAPK activation leads to permeabilization of outer mitochondrial membrane resulting in mitochondrial cytochrome c release into the cytosol during cell apoptosis progresses .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Bcl‐2/Bax ratio is very important in apoptosis regulation. The down‐regulation of Bcl‐2 protein and the up‐regulation of Bax protein can cause MOMP and induce cell apoptosis eventually (Kim et al, ). The present study showed an increasing expression of Bax at both mRNA and protein levels in GC‐2spd cells after exposure to DEHP, accompanying with the decreasing expression of Bcl‐2.…”
Section: Discussionmentioning
confidence: 99%